Pengaruh Kapabilitas Inovasi dan Etika Bisnis Terhadap Kepuasan Pelanggan Serta Dampaknya Terhadap Loyalitas Pelanggan - Fathorrahman Fathorrahman; Ummi Wahyuni; Zainurrafiqi Zainurrafiqi; Runik Puji Rahayu; Nurul Hidayati (BADAN PENERBIT STIEPARI PRESS, 2024)
This study aims to analyze the effect of innovation capability and business ethics on customer satisfaction and their impact on customer loyalty in batik SMEs in Pamekasan Regency. The research uses a quantitative approach with a survey method, involving 100 customers of batik SMEs as the sample. Data collection was carried out using a Likert scale questionnaire, and the collected data were analyzed using regression analysis to test the relationships between variables. The results show that innovation capability and business ethics have a significant positive effect on customer satisfaction. Furthermore, customer satisfaction was found to have a significant positive impact on customer loyalty. Innovation capability and business ethics also influence customer loyalty, mediated by customer satisfaction. These findings have important implications for batik SMEs in Pamekasan to strengthen innovation capability and business ethics in order to improve customer satisfaction and loyalty, which in turn will enhance their competitiveness in the market.